EPIDEMIOLOGICAL CHARACTERIZATION OF PORCINE TOXOPLASMOSIS IN THE “ALTO SERTÃO” REGION OF SERGIPE, NORTHEASTERN BRAZIL - Silva, José Eduardo Marques; Marinho, Glenda Lídice de Oliveira Cortez; Jusi, Márcia Mariza Gomes; da Silva, José Givanildo; Barbosa, Iago Carvalho; Azevedo, Sergio Santos de; Mota, Rinaldo Aparecido; Vieira, Rafael Felipe da Costa; Stipp, Danilo Tancler (Archives of Veterinary Science, 2019)
Toxoplasma gondii is the etiological agent of toxoplasmosis. Serological studies have demonstrated the parasite occurrence in swine from different regions; however there are no studies that can demonstrate epidemiological status of porcine toxoplasmosis in the Brazilian state of Sergipe. The study purposes were to verify the anti-Toxoplasma gondii antibodies presence and identify risk factors associated with infection in pigs. An amount of 230 blood samples of pigs over four months of age from 45 farms were collected and analyzed by indirect immunofluorescence antibody assay. An epidemiological questionnaire was applied on the properties of origin of the animals to identify risk factors associated with the infection. A seroprevalence of 8.3% with the titre ranging from 64 (15/230) to 1024 (02/230) was found. Animals from the municipalities of Poço Redondo and Canindé de São Francisco showed the highest prevalences, 18.52% (5/27) and 12.90% (4/31), respectively. The seroprevalence found was considered low when compared to previous studies performed in Brazil, particularly in the northeast region. The age of slaughtered animals should be considered and positive association between the variables age and T. gondii infection was found. Most of swine sampled (194/230) were up to six months which may also influence in the seroprevalence. A low anti-T. gondii seroprevalence was observed in the present study, however it is concluded that T. gondii infection is present in pigs population. The knowledge about its frequency contributes to the establishment of strategies for disease control by appliance of prevention measures in livestock production.